1984
DOI: 10.1210/jcem-59-6-1121
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Hyperinsulinemia of Simple Obesity: Pancreatic Hypersecretion or Impaired Insulin Metabolism?*

Abstract: Insulin and C-peptide levels in peripheral blood in the fasting state and after an oral glucose load were measured in 65 nondiabetic, obese subjects and 65 age- and sex-matched nondiabetic normal weight subjects. Fasting insulin and C-peptide levels were significantly higher in obese than in nonobese subjects, whereas 1 and 2 h after the oral glucose load only insulin concentrations were significantly higher in the obese subjects. C-peptide to insulin molar ratios, as well as the relation between the increment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
1

Year Published

1986
1986
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(34 citation statements)
references
References 37 publications
3
29
1
Order By: Relevance
“…Several crosssectional studies have confirmed these findings of basal hyperinsulinemia (3,13,14,31,38). Furthermore, higher insulin concentrations of obese subjects have been shown in response to various stimuli such as a meal (31,37) or an oral (3,13,28) or iv glucose load (17,18,27,31,41,42).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Several crosssectional studies have confirmed these findings of basal hyperinsulinemia (3,13,14,31,38). Furthermore, higher insulin concentrations of obese subjects have been shown in response to various stimuli such as a meal (31,37) or an oral (3,13,28) or iv glucose load (17,18,27,31,41,42).…”
Section: Discussionmentioning
confidence: 65%
“…On the other hand, it cannot totally be excluded that, due to BIA measurement in the present study, the change of body fat might have been underestimated. Basal hyperinsulinemia of obese subjects has been attributed to an increase of insulin secretion in most studies (3,13,14,31). An additional contribution of clearance was reported by Rossell et al (38).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Although they showed a normalization of insulin secretion rate, these studies could not separate the contribution from insulin sensitivity versus weight as both simultaneously improved. This issue is important because obesity has been implicated to increase insulin secretion (13,28,29). In addition, methods to estimate GS-ISR were different from the current study and used single glucose injection (10,12) or fixed glucose infusion (11) with subsequent quantification of C-peptide response.…”
Section: Discussionmentioning
confidence: 91%
“…Insulin metabolism was evaluated indirectly from the molar ratio of C-peptide to insulin at fasting and after ingestion of glucose as well as from the difference between incremental areas of C-peptide and insulin divided by incremental area of C-peptide. Such an approach was used by other investigators and our selves in studies concerning obesity [27][28][29][30][31], glucose intolerance [32][33][34], pregnancy [35], chronic liver dis ease [36][37][38][39], elderly subjects [40], hyperthyroidism [41 ]. as well as investigations in healthy subjects with a family history of diabetes [42,43] or undergoing a comparison between oral and intravenous glucose loads [44.…”
Section: Methodsmentioning
confidence: 99%